Implementation of Practices and Issues Regarding Blended Learning in High School Education during the COVID-19 Pandemic - Dusita Sirisakpanich (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present COVID-19 pandemic has brought extraordinary challenges and has affected the education sector, and no one knows when it will end. Every school has to adapt to the educational process called exclusively blended teaching and learning as the “new normal education policy”. In this regard, this article was conducted to explore the constraints of blended education during the COVID-19 pandemic in Thailand. This present article was also desired to provide a baseline support structure that will assist teachers in an efficient transition to a blended learning approach. Since the concept of integrating co-teaching and blended learning is a new teaching model implemented during the pandemic crisis, it is important to review how a blended learning environment impacts the experience of teachers and students. A blended learning approach in fact is relatively new to the Thai educational system. It offers the opportunity for educators to develop new methods of communication with and among students, improve learning activities that are engaging to the digital native learner, and differentiate instruction to meet the needs of the diverse learners’ styles presented in any classroom. In the blended based learning, it is necessary to build opportunities for interactions and communications between students and their instructors. Synchronous and asynchronous forms are also possible tools to reach the needed interactivity levels to enhance retention rate of students, support students in need, and replace individual face-to-face support and mentoring provided in conventional learning on-campus.